2011
DOI: 10.2174/1876526201104010001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Reactive Oxygen Species and Collagen Synthesis by Angiotensin II in Cardiac Fibroblasts

Abstract: Angiotensin II increases the NAD(P)H-dependent superoxide anion production and the intracellular generation of reactive oxygen species in cardiac fibroblasts and apocynin, a NAD(P)H oxidase inhibitor, abrogates this rise. The membrane associated NAD(P)H oxidase complex is the predominant source of superoxide anion and reactive oxygen species generation in angiotensin II-stimulated adult cardiac fibroblasts. Inhibition of this NAD(P)H oxidase complex with apocynin completely blocks the angiotensin II-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 178 publications
2
5
0
Order By: Relevance
“…Consistent with the previous studies (Chen et al, ; Yang et al, ; Lijnen, ), in the present experiment, we found that the expression of MMP‐1 was reduced but expressions of TIMP‐1 and TGF‐β1 were increased by Ang II. In addition, we found for the first time that levels of MMP‐1 could be increased ( in vitro and in vivo ) but TIMP‐1 ( in vitro ) and TGF‐β1 ( in vitro and in vivo ) could be decreased by pre‐miR‐214 treatment, and these effects were blocked almost completely by anti‐miR‐214 treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with the previous studies (Chen et al, ; Yang et al, ; Lijnen, ), in the present experiment, we found that the expression of MMP‐1 was reduced but expressions of TIMP‐1 and TGF‐β1 were increased by Ang II. In addition, we found for the first time that levels of MMP‐1 could be increased ( in vitro and in vivo ) but TIMP‐1 ( in vitro ) and TGF‐β1 ( in vitro and in vivo ) could be decreased by pre‐miR‐214 treatment, and these effects were blocked almost completely by anti‐miR‐214 treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Also, we chose a relatively lower concentration of Ang II, which may cause nearly 50% increased cell vitality. Similar findings have also been described by Lijnen et al (Li et al, ; Lijnen, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In previous studies [40,41], Ang II has been shown to increase collagen synthesis. In previous studies [40,41], Ang II has been shown to increase collagen synthesis.…”
Section: Discussionmentioning
confidence: 85%
“…Increased collagen deposition may be due to oxidative stress that stimulates the expression of genes involved in collagen biosynthesis (Guler et al, 2009). Moreover, inhibition of superoxide dismutase (antioxidant enzyme) stimulates collagen production and this demonstrated a vital role of superoxide dismutase and the generated reactive oxygen species (ROS) in collagen accumulation (Lijnen et al, 2011). Results of the current study revealed increased PAS +ve materials in the thickened walls of bronchioles, arteries and alveolar septae with moderately stained granuloma areas in lungs of pregnant rats of groups S1, S2 and revealed decreased PAS +ve materials in the fetuses of S1, S2 groups in a dose dependent manner as compared to control group.…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%